Comparing the role of annealing on the transport properties of polymorphous AgBiSe2 and monophase AgSbSe2. Issue 13 (13th February 2018) - Zou, Minmin; Liu, Qing; Wu, Chao-Feng; Wei, Tian-Ran; Tan, Qing; Li, Jing-Feng; Chen, Fei
Abstract : Annealing treatment has different impact on the transport properties of polymorphous AgBiSe2 and monophase AgSbSe2 . Abstract : AgBiSe2 and AgSbSe2, two typical examples of Te-free I–V–VI2 chalcogenides, are drawing much attention due to their promising thermoelectric performance. Both compounds were synthesized via melting and consolidated by spark plasma sintering. The role of annealing on the transport properties of polymorphous AgBiSe2 and monophase AgSbSe2 was studied. Annealing has a greater impact on AgBiSe2 than AgSbSe2, which is ascribed to the temperature dependent phase transition of AgBiSe2 . Unannealed AgBiSe2 shows p–n switching, but annealed AgBiSe2 exhibits n-type semiconducting behavior over the whole measurement temperature range. By performing high-temperature Hall measurements, we attribute this intriguing variation to the change in the amount of Ag vacancies and mid-temperature rhombohedral phase after annealing. Both AgBiSe2 and AgSbSe2 exhibit low thermal conductivity values, which are ∼0.40–0.50 W m −1 K −1 for AgSbSe2 and ∼0.45–0.70 W m −1 K −1 for AgBiSe2, respectively. The maximum ZT value of AgBiSe2 is enhanced from 0.18 to 0.21 after annealing. Pristine AgSbSe2 presents a ZT value as high as 0.60 at 623 K, although slight deterioration emerges after annealing.